2021
DOI: 10.26740/bioedu.v11n1.p206-217
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Perangkat Pembelajaran Biologi Berbasis Sains Teknologi Masyarakat dan Lingkungan Kelas X SMA

Abstract: Sains Teknologi Masyarakat dan Lingkungan merupakan model pembelajaran yang mengarahkan peserta didik  untuk membahas isu permasalahan nyata lingkungan mengenai proses, dampak, dan gagasan pemecahan masalah. Keberhasilan dari proses pembelajaran dipengaruhi oleh pemilihan model ataupun pendekatan pembelajaran yang sesuai dengan materi dengan mempertimbangkan kemampuan yang ingin dicapai oleh peserta didik serta bisa dirancang dalam suatu perangkat pembelajaran berdasarkan kurikulum 2013. Adapun tujuan dari pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…While Maemunah et al (2013) from the results of their research concluded that there was a significant difference in increasing the creativity of students who applied the science, technology, and society model during learning and did not apply the science, technology, and society model during learning Agustini et al (2013), Suarni et al (2021), Fauziah et al (2021 and Afni et al (2017) from the results of their research said that students' mastery of physics concepts taught by the science, technology, and society model was higher than students' mastery of physics concepts taught using conventional methods. On the other hand, Amalini et al (2021) says learning by using science, technology, and society learning for science process skills can significantly improve learning outcomes, activities and student responses.…”
Section: Resultsmentioning
confidence: 99%
“…While Maemunah et al (2013) from the results of their research concluded that there was a significant difference in increasing the creativity of students who applied the science, technology, and society model during learning and did not apply the science, technology, and society model during learning Agustini et al (2013), Suarni et al (2021), Fauziah et al (2021 and Afni et al (2017) from the results of their research said that students' mastery of physics concepts taught by the science, technology, and society model was higher than students' mastery of physics concepts taught using conventional methods. On the other hand, Amalini et al (2021) says learning by using science, technology, and society learning for science process skills can significantly improve learning outcomes, activities and student responses.…”
Section: Resultsmentioning
confidence: 99%
“…Choosing the right language will help students understand the concept and prevent errors in understanding the sentences conveyed (Sihafudin et al, 2020). Student worksheet will be easy to read and understand if it uses clear letters, numbers, and sentences (Amalini et al, 2021). Important language elements that should be avoided include the use of words that are unclear, ambiguous, difficult to understand, have double meanings, are not adjusted to the Pedoman Umum Ejaan Bahasa Indonesia (PUEBI), and do not use correct spelling (Syamsi et al, 2021).…”
Section: Developmentioning
confidence: 99%
“…Untuk meningkatkan capaian pengetahuan lingkungan maka perlu terus dilakukan inovasi. Rimas (2016) 13 menyebutkan bahwa pembelajaran PLH yang baik seharusnya menggunakan model pembelajaran seperti Problem Based Learning (PBL), Discoveries, dan Inkuiri. Bahkan Jika langsung mengkaji masalah lingkungan nyata yang ditemukan di kehidupan sehari-hari, PLH dapat mempermudah pencapaian keterampilan tingkat tinggi (higher order skill) seperti: berpikir kritis, berpikir kreatif, berpikir secara integrative, dan memecahkan masalah.…”
Section: Pendahuluanunclassified